2023
DOI: 10.1186/s12905-023-02755-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting quality of life in women with breast cancer: a path analysis

Farnaz Faroughi,
Azita Fathnezhad-Kazemi,
Parvin Sarbakhsh

Abstract: Background Breast cancer may negatively affect people’s quality of life. We investigated the predictors of quality of life in women with breast cancer with the mediating role of resilience. Method In a cross-sectional design, 218 patients completed a survey referring to the Valiasr International Hospital Oncology Center in Tabriz, Iran. Four validated self-report measures assessed HRQoL as measured by the SF-12, Resilience, Hope, and Perceived Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…A recent study that explored the role of social support in the relationship between resilience, hope and QoL in patients with breast cancer concluded that all three variables had a significant effect on health-related QoL [ 69 ]. Other studies also reinforce the importance of social support in improving the QoL of patients, as it can influence the process of adaptation to cancer diagnosis and treatment [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study that explored the role of social support in the relationship between resilience, hope and QoL in patients with breast cancer concluded that all three variables had a significant effect on health-related QoL [ 69 ]. Other studies also reinforce the importance of social support in improving the QoL of patients, as it can influence the process of adaptation to cancer diagnosis and treatment [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the latest data from the International Agency for Research on Cancer (IARC), the number of new breast cancer patients worldwide reached 2.26 million in 2020 (Ferlay et al, 2021). Of these, more than 1.1 million women are newly diagnosed with breast cancer globally each year, and 410,000 women die from the disease ( Faroughi et al, 2023 ). And Chinese women with breast cancer account for about 18% of global BC deaths ( Cao et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%